Association among raised intraventricular pressure, clinical signs, and magnetic resonance imaging findings in dogs with congenital internal hydrocephalus - Daniela Farke; Agnieszka Olszewska; Kathrin Büttner; Martin J. Schmidt (Journal of Veterinary Internal Medicine)
Abstract Background Dogs with internal hydrocephalus do not necessarily have high intraventricular pressure (IVP). Hypothesis/Objectives Not all reported MRI findings indicate high IVP and some clinical signs might be associated with elevated IVP and syringomyelia. Animals Fifty‐three dogs. Materials and Methods Cross‐sectional study. Clinical signs and MRI findings were evaluated for an association of IVP >12 mm Hg and syringomyelia. Results High IVP was associated with obtundation OR 4.64 (95% CI 1.27‐16.93) (P = .02), head tilt OR 6.42 (95% CI 1.08‐37.97) (P = .04) and nystagmus OR 8.24 (95% CI 1.44‐47.07) (P = .02). Pain was associated with syringomyelia OR 3.4 (95% CI 0.98‐11.78) (P = .05). The number of affected ventricles was associated with high IVP OR 2.85 (95% CI 0.97‐8.33) (P = .05) and syringomyelia OR 12.74 (95% CI 2.93‐55.4) (P = .0007). Periventricular edema OR 24.46 (95% CI 4.54‐131.77), OR 7.61 (95% CI 1.91‐30.32) (P < .0002, P = .004) and signal void sign OR 17.34 (95% CI 4.01‐74.95), OR 4.18 (95% CI 1.16‐15.02) (P < .0001, P = .03) were associated with high IVP and syringomyelia. The probability for syringomyelia is lower with disruption of the internal capsule OR 0.19 (95% CI 0.05‐0.72) (P = .01) and higher VBR OR 0.25 (95% CI 0.1‐0.63) (P = .004). Conclusions and Clinical Importance Previously reported MRI findings are not predictive of high IVP. Clinical signs and MRI findings should be used to make a diagnosis of internal hydrocephalus in dogs with or without high IVP.